Examining the Risk Behaviors of Individuals with Ultimatum Game within the Framework of House Money Effect - TEPELER, Muhammed İkbal; DAŞTAN, Hüseyin (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The aim of this study is to find out the behavior of the economic individual from the assumption of rationality accepted in the standard economic theories and to show that the behavior of the individual is not completely rational and the cognitive capacity is limited. When the assumption of rationality which is the starting point of behavioral economics is questioned, the main aim is not to completely disagree with standard economic theories. On the contrary, it is aimed to support the standard economic theory with a more realistic prediction in the light of experimental methods. Scope of the study, basic assumptions and concepts in mainstream economics and behavioral economics examined and compared. The basic issues in the psychological foundations of mainstream economics, the processes of behavioral and mainstream economics from the past to the present day, and the behavioral economics literature discussed in detail. Finally, the phenomenon of "House Money Effect" from mental accounting cases was experimentally analyzed with the help of ultimatum game. Keywords: Behavioral Economics, Ultimatum Game, House Money Effect